IN VITRO ASSESSMENT OF CYTOTOXICITY AND OXIDATIVE STRESS PARAMETERS OF NATURAL RUBBER LATEX MEMBRANES STABILIZED WITH DIFFERENT CONCENTRATIONS OF AMMONIA IN CHO-K1 CELLS - Caroline de Souza Araujo; Dalita Gomes Silva Morais Cavalcante; Nathália Oliveira Braga; Andressa Silva Gomes; Eidi Yoshihara; Leandra Ernst Kerche; Aldo Eloizo Job (Colloquium Vitae, 2020)
The purpose of this study was to assess in vitro cytotoxicity of natural rubber (NR) latex membranes stabilized with different concentrations of ammonia, as well as evaluate possible changes in oxidative stress parameters. To this end, CHO-k1 cells were exposed to NR membranes for 24 h. Cytotoxicity was assessed by the MTT assay and the oxidative stress parameters were established by glutathione (GSH) and malondialdehyde (MDA) levels. The results show that the ammonia present in the NR latex membranes can deplete cell viability and enhance GSH consumption in the cells. NR latex membranes stabilized with 2.00% of ammonia were cytotoxic to the cell lineage used in this study. From these results, it is possible to infer that the use of ammonia to stabilize NR latex membranes with biomedical purposes has to be done carefully, to avoid possible harmful effects to human health.